2006
DOI: 10.1002/gps.1737
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cognitive and functional impairment in a community sample in Ribeirão Preto, Brazil

Abstract: CFI prevalence results were similar to those found by studies in Brazil, Puerto Rico and Malaysia. Cognitive and functional impairment is a rather heterogeneous condition which may be associated with various clinical conditions found in the elderly population. Due to its high prevalence and association with higher mortality and disability rates, this clinical syndrome should receive more attention on public health intervention planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
2
17

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 30 publications
7
37
2
17
Order By: Relevance
“…Considering specific diagnosis, CI prevalence found in the present study was higher than that found in a Brazilian community report on this issue (1.6%) (20) . Dementia prevalence was much higher than in other Brazilian studies (range from 7.1% to 7.2%), being this finding already expected (21)(22)(23) . It is known that MCI diagnosis is the basis for early detection of CI, although there is no consensus about this diagnostic process improvement.…”
Section: Discussionsupporting
confidence: 50%
“…Considering specific diagnosis, CI prevalence found in the present study was higher than that found in a Brazilian community report on this issue (1.6%) (20) . Dementia prevalence was much higher than in other Brazilian studies (range from 7.1% to 7.2%), being this finding already expected (21)(22)(23) . It is known that MCI diagnosis is the basis for early detection of CI, although there is no consensus about this diagnostic process improvement.…”
Section: Discussionsupporting
confidence: 50%
“…Only eight articles [7][8][9][10][11][12][13][14] complied with the inclusion and exclusion criteria. Three additional papers [24][25][26] were identified from the references.…”
Section: Resultsmentioning
confidence: 99%
“…A visual inspection of the meta-analysis suggested that there was high heterogeneity between the study results ( Figure 2A). The meta-regression indicated that the Full-text articles assessed for eligibility (n=18) 1,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Records included by reference searching (n=3) [24][25][26] Studies included in qualitative synthesis (n=11) [7][8][9][10][11][12][13][14][24][25][26] Full-text articles excluded (n=10) 1,15-23 Secondary analysis (n=8) 15,16,[18][19][20][21][22][23] Review article (n=2) 1,17 Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The sample had a mean age of 70.9 years (60 to 100; SD = 7.7), 63.4% were female, 10.1% were illiterate, and 62.2% had up to 8 years of education 14 .…”
Section: Sample Selectionmentioning
confidence: 99%